LeptoDB: an integrated database of genomics and proteomics resource of Leptospira. (12th June 2018) - Beriwal, Shruti; Padhiyar, Nikhil; Bhatt, Deven; Pandit, Prabhakar D; Ansari, Afzal; Lata, Kumari Snehkant; Saiyed, Zuber M; Vaghasia, Vibhisha; Sharma, Priyanka; Bhairappanavar, Shivarudrappa B; Soni, Subhash; Das, Jayashankar
Abstract: Leptospirosis is a potentially fatal zoo-anthroponosis caused by pathogenic species of Leptospira belonging to the family of Leptospiraceae, with a worldwide distribution and effect, in terms of its burden and risk to human health. The 'LeptoDB' is a single window dedicated architecture (5 948 311 entries), modeled using heterogeneous data as a core resource for global Leptospira species. LeptoDB facilitates well-structured knowledge of genomics, proteomics and therapeutic aspects with more than 500 assemblies including 17 complete and 496 draft genomes encoding 1.7 million proteins for 23 Leptospira species with more than 250 serovars comprising pathogenic, intermediate and saprophytic strains. Also, it seeks to be a dynamic compendium for therapeutically essential components such as epitope, primers, CRISPR/Cas9 and putative drug targets. Integration of JBrowse provides elaborated locus centric description of sequence or contig. Jmol for structural visualization of protein structures, MUSCLE for interactive multiple sequence alignment annotation and analysis. The data on genomic islands will definitely provide an understanding of virulence and pathogenicity. Phylogenetics analysis integrated suggests the evolutionary division of strains. Easily accessible on a public web server, we anticipate wide use of this metadata on Leptospira for the development of potential therapeutics. Database URL: http://leptonet.org.in